Resource Management for Sustainable Agriculture - Abrol, Vikas; Sharma, Peeyush (IntechOpen, 2012)
In this book, papers pertaining to resource management for sustainable agricultural development are presented in four parts divided into ten chapters. Part I discusses the usage of water and waste management for sustainable agricultural development including aspects like irrigation management to prevent soil and ground water salinization, production of solid fuel from oil palm waste, sustainable ecomaterials and biorefinery from agroindustrial waste, nonpoint pollution from agriculture and livestock activities on surface water. Part II discusses sustainable management of dryland resources especially carbon sequestration under changing climate scenario. Part III deals with efficient nutrient management for sustainable crop productivity in different agro-climatic conditions, soil quality and productivity improvement under rainfed conditions. Part IV throws light upon effect of conservation tillage on soil properties and impact of agricultural traffic and tillage on soil properties.